Larval ultrastructure of Parasarcophaga dux (Thomson) (Diptera: Sarcophagidae) - Sukontason K. (2014)
Ultrastructure of all larval instars of Parasarcophaga dux (Thomson), a common flesh fly species in Thailand, is presented using scanning electron microscopy. Special attention is given to the structure of anterior and posterior spiracles since these are important features used to differentiate between other sarcophagids. Each anterior spiracle in second and third instars has a single row of papillae varying in number from 14 to 17. The posterior spiracular discs have incomplete peritremes, with a prominent inner arc. Three long, narrow spiracular slits are oriented more or less vertically in each spiracular disc of third instar. Posterior spiracular hairs lack extensive branching and emanate approximately midway down the length of each slit. Microscopic morphology of the mouthhooks markedly differs between the first and second instars. The structure of these mouthhooks supports this fly species as being necrophagous or capable of producing myiasis. © 2003 Elsevier Ltd. All rights reserved.